Assessing the role of innovative therapeutic paradigm on multiple sclerosis treatment response. (22nd July 2018) - Romeo, Marzia A. L.; Martinelli, Vittorio; Dalla Costa, Gloria; Colombo, Bruno; De Feo, Donatella; Esposito, Federica; Ferrè, Laura; Guaschino, Clara; Guerrieri, Simone; Liberatore, Giuseppe; Martinelli Boneschi, Filippo; Merlini, Arianna; et al.
Abstract : Objective: Within the last decade, many changes have been made to the management of patients with multiple sclerosis (MS). The aim of our study was to investigate the global impact of all these changes on the disease's course. Materials and methods: This single‐centre study was carried out on patients with multiple sclerosis (pwMS) who started treatment with first‐line disease‐modifying therapies. We have compared three large cohorts of patients with MS diagnosis, for three consecutive periods within July 2001, August 2001‐December 2005, and January 2006‐September 2011. Results: A total of 1068 relapsing‐remitting pwMS cases were included. Patients in the last cohort began treatment earlier ( P  < 0.0001), started more frequent treatment with high‐dose interferon beta or glatiramer acetate ( P  < 0.0001), and had experienced a more frequent treatment escalation strategy ( P  = 0.004) than patients in other cohorts. The multivariate analysis adjusted for baseline characteristics showed that pwMS of the last cohort had a high probability of showing no evidence of disease activity (NEDA3) at 4 years (OR 3.22, 95% CIs 1.89‐5.47; P  < 0.0001). These results were confirmed in a propensity score analysis. Conclusions: Our study showed an improvement over the last 15 years in the treatment response; this observation can be associated to a paradigm shift in MS treatment strategies.